Polyhydroxyalkanoate involvement in stress-survival of two psychrophilic bacterial strains from the High Arctic - Grzesiak, Jakub; Rogala, Małgorzata Marta; Gawor, Jan; Kouřilová, Xenie; Obruča, Stanislav (Applied microbiology and biotechnology, 2024)
An ever-growing body of literature evidences the protective role of polyhydroxyalkanoates (PHAs) against a plethora of mostly physical stressors in prokaryotic cells. To date, most of the research done involved bacterial strains isolated from habitats not considered to be life-challenging or extremely impacted by abiotic environmental factors. Polar region microorganisms experience a multitude of damaging factors in combinations rarely seen in other of Earth's environments. Therefore, the main objective of this investigation was to examine the role of PHAs in the adaptation of psychrophilic, Arctic-derived bacteria to stress conditions. Arctic PHA producers: Acidovorax sp. A1169 and Collimonas sp. A2191, were chosen and their genes involved in PHB metabolism were deactivated making them unable to accumulate PHAs (ΔphaC) or to utilize them (Δi-phaZ) as a carbon source. Varying stressors were applied to the wild-type and the prepared mutant strains and their survival rates were assessed based on CFU count. Wild-type strains with a functional PHA metabolism were best suited to survive the freeze-thaw cycle - a common feature of polar region habitats. However, the majority of stresses were best survived by the ΔphaC mutants, suggesting that the biochemical imbalance caused by the lack of PHAs induced a permanent cell-wide stress response thus causing them to better withstand the stressor application. Δi-phaZ mutants were superior in surviving UV irradiation, hinting that PHA granule presence in bacterial cells is beneficial despite it being biologically inaccessible. Obtained data suggests that the ability to metabolize PHA although important for survival, probably is not the most crucial mechanism in the stress-resistance strategies arsenal of cold-loving bacteria. KEY POINTS: • PHA metabolism helps psychrophiles survive freezing • PHA-lacking psychrophile mutants cope better with oxidative and heat stresses • PHA granule presence enhances the UV resistance of psychrophiles.
Keywords: Carbon; uhlík; Bacteria; polyhydroxyalkanoáty; Polyhydroxyalkanoates